Physical activity and depression of Chinese college students: chain mediating role of rumination and anxiety - Liu, Yanying; Feng, Qingkun; Guo, Kelei (Frontiers in Psychology, 2023)
Objective To explore the relationship between physical activity and depression among college students, as well as the mediating role of rumination and anxiety. Methods A total of 1,292 Chinese college students were investigated by physical activity questionnaire, rumination scale, self-rating anxiety scale (SAS), and depression scale. Results (1) There was a significant negative correlation between physical activity and depression (r = −0.399, p < 0.01), and the direct path of physical activity on depression was significant (β = −0.399, t = −13.374, p < 0.01). (2) Physical activity negatively predicted rumination (β = −0.322, t = −10.440, p < 0.01) and anxiety (β = −0.222, t = −7.089, p < 0.01). Rumination positively predicted anxiety (β = 0.283, t = 9.017, p < 0.01) and depression (β = 0.267, t = 9.046, p < 0.01). Anxiety positively predicted depression (β = 0.262, t = 8.902, p < 0.01). (3) Rumination and anxiety play a significant mediating role between physical activity and depression. The mediating effect involves three paths: physical activity → rumination → depression (the mediating effect value: −0.076); physical activity → anxiety → depression (the mediating effect value: −0.052). Physical activity → rumination → anxiety → depression (the mediating effect value: −0.021). Conclusion (1) Physical activity can negatively predict the rumination, anxiety, and depression of college students, which means physical activity can reduce rumination, anxiety, and depression of college students. (2) Physical activity can not only directly affect the depression of college students, but also indirectly affect depression through the independent intermediary role of rumination and anxiety, and the chain mediation of rumination and anxiety.